A method to evaluation rock brittleness based on statistical damage constitutive parameters - Gao, Meiben; Li, Tianbin; Gao, Yang; Zhang, Yan; Yang, Qingwen; He, Zhihao; He, Qingqing (Frontiers in Earth Science, 2023)
Brittleness is an important parameter to evaluate the performance of rock engineering. A scientific and reasonable brittleness evaluation method is of great significance to theoretical research and the engineering practice of rock mechanics. In view of the existing statistical constitutive models of rock based on the Weibull distribution being able to express various constitutive behaviors well, such as brittleness, plasticity, strain softening, this paper want to determine rock brittleness from constitutive models. First, the parameter m, which can effectively reflect the overall characteristics of the rock stress-strain curve, and the parameter δ, which can reflect the post-peak characteristics, are selected. Then, a brittle evaluation method based on rock statistical damage constitutive parameters is proposed, and the brittleness index Bm (Bm = m·δ) is established. The feasibility is verified by the testing data of granite, sandstone and marble under different conditions. The results show that the brittleness of those hard rocks decrease with the increasing of confining pressure. For confining pressures of 5 MPa and 15 MPa, the brittleness of granite under triaxial unloading test is greater than that under triaxial compression test. The calculation results quantitatively reflect the brittle characteristics of sandstone, marble and granite in the test. Compared with the existing representative brittleness indexes，it is found that the brittleness index Bm can effectively reflect the characteristics of rock brittleness decreasing with increasing confining pressure and enhancement under unloading stress path. This paper provides a way to evaluate rock brittleness from the perspective of a constitutive model, which is helpful to enrich our understanding of rock brittleness.